Influence of impurities on the electrochemistry of carbon nanotubes and the toxicity of nanomaterials - Chng, Elaine Lay Khim (2015)
Carbon nanomaterials such as carbon nanotubes and graphene are well recognized for their exceptional physical, structural and electronic properties that can be exploited for a wide range of electrochemical and biomedicine applications. Owing to the inherent electrocatalytic property of carbon nanotubes, their application as an electrochemical material has reportedly led to lowered overpotentials as well as enhanced redox reactions. However, all of these were elucidated to be due to the presence of metallic and carbonaceous impurities within carbon nanotubes which acted as electroactive sites. This project will expand on the influence of impurities on the electrochemistry of carbon nanotubes, and introduce an improved purification technique for an efficient removal of these impurities. With the subsequent discovery of graphene, their potential use in applications was modelled after carbon nanotubes. Along with the advent of graphene synthesis methods, numerous graphene-family nanomaterials were produced and these were explored for their use in numerous biomedicine applications. Consequently, concerns were raised about their possible nanotoxicological impact but the variations in their physiochemical properties have made it challenging to evaluate their toxicities. This project will investigate the toxicity effects of multiple derivatives of graphene, and this is also extended to include molybdenum sulfide which is another 2D material as well as nanomotors. All these are integral to the continuing efforts on nanosafety research as part of the rapid advancements in nanotechnology.